Bioengineered platelet nanoplatform enables renal-targeted dexamethasone delivery for chronic nephritis therapy with dual anti-inflammatory/anti-fibrotic effects and minimized systemic toxicity - Lingling Zhang; Haifeng Gong; Xuelian Gong; Bing Zhou; Xijian Wang; Shengnan Fei; Donglin Xia; Chunyang Xu; Xinzhong Huang (Bioactive Materials)
Chronic nephritis management remains challenging due to the compromised therapeutic efficacy and severe systemic complications of conventional glucocorticoid therapy. Here, we developed a bioinspired platelet-mediated delivery system (LN-DEX@PLT) that leverages platelet tropism toward injured glomeruli for precision drug delivery. This system integrates lipid nanoemulsion encapsulation with platelet-mediated hitchhiking delivery to achieve three key functionalities: (1) enhanced renal targeting demonstrated by 2.2-fold higher glomerular accumulation compared to free dexamethasone via In vivo imaging, (2) effective mitigation of glucocorticoid-induced metabolic toxicity evidenced by reduced fasting plasma glucose (5.2 ± 0.3 vs 8.3 ± 0.7 mmol/L in free DEX), suppression of hepatic gluconeogenic enzymes (PEPCK expression decreased by 43 %, G-6 Pase by 51 %, both p < 0.001), and suppressed body weight (−23.1 % versus free DEX group), and (3) dual-pathway therapeutic effects through IL-6/TNF-α suppression and p53-p21Cip1-mediated senescence delay. In Adriamycin-based chronic nephritis models, LN-DEX@PLT demonstrated superior renal protection with 81 % reduction in proteinuria (vs 33 % for free DEX). In LPS-induced and Adriamycin-based chronic nephritis models, LN-DEX@PLT demonstrated suppression of renal inflammation markers (IL-6 expression decreased to 68 %, TNF-α to 51 %) and macrophage infiltration (F4/80+ cells decreased 5.3-fold). This platelet-biohybrid system provides a clinically translatable paradigm for precision glucocorticoid therapy with reduced dosing frequency.